2021
DOI: 10.2147/rru.s322822
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of PUV Patients Following Ablation in a Tertiary Teaching Hospital in Addis Ababa, Ethiopia

Abstract: Background: Posterior urethral valve (PUV) is the most common cause of congenital lower urinary tract obstruction in boys. It is considered that early diagnosis and intervention have good outcomes in terms of renal function, though the varying extent of embryological insult requires these boys to remain in extended follow-up and care. Objective: To assess the renal outcome of patients following PUV ablation. Methods: This was a descriptive retrospective study. Data were collected from the operation logbooks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Five studies analyzed the association between nadir creatinine and the development of CKD ( 27 , 29 , 33 , 34 , 36 ), five studies analyzed the association between nadir creatinine and the development of ESKD ( 26 , 30 , 31 , 32 , 35 ), and remaining three studies analyzed the association between nadir creatinine and the development of CKD and ESKD separately ( 28 , 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies analyzed the association between nadir creatinine and the development of CKD ( 27 , 29 , 33 , 34 , 36 ), five studies analyzed the association between nadir creatinine and the development of ESKD ( 26 , 30 , 31 , 32 , 35 ), and remaining three studies analyzed the association between nadir creatinine and the development of CKD and ESKD separately ( 28 , 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies performed a multivariable analysis to screen potential confounders with the common result that nadir creatinine was an independent factor for the development of CKD. Other prognostic factors identified were proteinuria ( 27 , 37 ), mild-to-severe bladder dysfunction ( 26 , 31 , 32 ), baseline creatinine ( 28 , 37 , 38 ), hypertension ( 37 ), recurrent urinary tract infection (UTI), polyuria ( 32 ), delay of intervention ( 27 ), high-grade vesico-ureteral reflux (VUR), prenatal diagnosis, renal echography abnormality, prematurity ( 28 ), creatinine at 6 weeks from the surgical ablation ( 38 ), and mechanical ventilation ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteinuria is a common marker in nephrology that is used to assess kidney damage. Several studies have identified proteinuria as a negative prognostic marker for renal outcome in PUV patients [ 36 , 62 , 66 , 67 ]. Some studies have shown that urinary markers of inflammation and fibrotic remodelling can predict renal outcome.…”
Section: Prognostic Factors For Chronic Kidney Disease Developmentmentioning
confidence: 99%
“…Lulseged (1987) also stated that oat is a dual purpose forage crop which can also be used as human food in many parts of the world. According to the Ethiopia Ministry of agriculture and rural development, oats was registered as grass and used as forages (Getnet, 2012). Oats are abundantly grown in the central highlands of Selale and some parts of west Shewa like Meta-Robi and Galessa areas of Dendi woreda, Arsi, Bale and Gojjam.…”
Section: Introductionmentioning
confidence: 99%